1993
DOI: 10.1172/jci116568
|View full text |Cite
|
Sign up to set email alerts
|

Transbilayer mobility and distribution of red cell phospholipids during storage.

Abstract: We studied phospholipid topology and transbilayer mobility in red cells during blood storage. The distribution of phospholipids was determined by measuring the reactivity of phosphatidylethanolamine with fluorescamine and the degradation of phospholipids by phospholipase A2 and sphingomyelinase C. Phospholipid mobility was measured by determining transbilayer movements of spin-labeled phospholipids. We were unable to detect a change in the distribution of endogenous membrane phospholipids in stored red cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 39 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…Although PS externalization has been shown in cases of in vitro RBC storage and vesiculation, 28 conflicting results have appeared in studies carried out in blood bank ex vivo conditions. 12,31,42 Older studies have asserted that the caspases of mature RBCs can be functionally active only in vitro and not in intact RBCs, either during prolonged storage or in response to various proapoptotic stimuli. 39 Our studies have shown that in conditions used for transfusion, the caspase 3 and probably other caspases can be activated in whole cells.…”
Section: Apoptosismentioning
confidence: 99%
“…Although PS externalization has been shown in cases of in vitro RBC storage and vesiculation, 28 conflicting results have appeared in studies carried out in blood bank ex vivo conditions. 12,31,42 Older studies have asserted that the caspases of mature RBCs can be functionally active only in vitro and not in intact RBCs, either during prolonged storage or in response to various proapoptotic stimuli. 39 Our studies have shown that in conditions used for transfusion, the caspase 3 and probably other caspases can be activated in whole cells.…”
Section: Apoptosismentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Briefly, it is considered that RCMVs result from ecchinocytic changes in stored RBCs. 12 Ecchinocytic changes are protrusions of the outer leaflet of the RBC membrane and are related to a loss of phosphatidylinositol-4-phosphate and phosphadidylinositol-4,5-diphosphate and an increase in diacylglycerol in the inner leaflet of the cell membrane, [15][16][17] partly due to a calcium influx and partly due to ATP depletion. 18 Associated with this, a loss of membrane phospholipid asymmetry occurs, with expression of anionic phospholipids, such as phosphatidylserine (PS), on the surface of the outer leaflet.…”
mentioning
confidence: 99%
“…For this purpose an in vitro system was devised in which the transmembrane movement of endogenously synthesized, radiolabeled PE could be monitored using the amino-reactive probe fluorescamine. This chemical reacts very rapidly with amino groups at slightly alkaline pH (16) and has been successfully used in determining the transmembrane distribution of PE in several organelles and plasma membranes (17)(18)(19)(20). Due to the high amount of PE present in the inner membrane of wild type E. coli, steric interference of the fluorescamine derivative of PE is likely to prevent the reaction of the newly synthesized radiolabeled PE with fluorescamine from going to completion (21).…”
mentioning
confidence: 99%